Perfil da violência sexual contra crianças e adolescentes em Sergipe : dados da capital e do interior - Oliveira, Laíze Fonseca (2013)
Violence against children and teenagers includes situations of sexual abuse both inside and outside the family, as well as situations concerning sexual exploitation where a mercantile dimension is clearly present. This study was performed by means of a documental research involving 579 cases registered in 2010 and 2011 in the Serviço de Atendimento a Vítimas de Violência Sexual de Sergipe (SAVVS), located at Maternidade Nossa Senhora de Lourdes (MNSL), and also 222 cases extracted from police records from the Delegacia de Atendimento aos Grupos Vulneráveis (DAGV), aiming at analyzing and characterizing situations of sexual violence against children and teenagers. The characterization of the cases registered at SAVVS implies that 86,5% of victims are female, 56,5% are children (61,5% in the countryside and 32,1% in the capital), and 89,7% of perpetrators are people known to the victim, 94,1% being male. 31,4% of the perpetrators are victims relatives. As to the places where the aggression were committed, it is worth noting that 62,2% of victims were assaulted at their family s residence. There were no significant differences concerning the age of victims in the countryside or the capital, just as there was no difference concerning the place where aggression was perpetrated and the characterization of aggressors in the countryside and the capital. A comparison concerning the service flow was also drawn, with the purpose of knowing if victims searched for continued service after leaving the police station, and the result indicates that only in 176 out of 222 cases the victims maintained a continued service process and went to the SAVVS. In general, results point to a characterization of sexual violence in Sergipe according to what the scholarship states about other areas in Brazil, with similar dynamics between countryside and capital. This study can be seen as the first one which is dedicated to statistics of sexual violence against children and teenagers in the past few years in the state of Sergipe. Therefore, it shall contribute to the development of strategies to protect children and teenagers, providing scientific foundations to interventionist actions.